EXTERNAL GOVERNMENT DEBT MANAGEMENT OF UKRAINE IN CONDITIONS OF SOCIAL AND ECONOMIC AND PANDEMIC SHOCKS - MOROZ, Ivanna (Scientific journal «World of Finance», 2021)
Introduction. The consequences of the COVID-19 pandemic on macroeconomic dynamics and the state of external public debt are analised. The main reasons for the growth of the State Budget deficit of Ukraine are identified and the need to increase the efficiency of the external public debt management policy in the context of minimizing the budget deficit is proved. Emphasis is placed on the situational and imbalance of Ukraine’s external public debt management policy, which is due to the lack of the Economic Development Strategy of Ukraine and the Government’s program of activities for 2020. It is substantiated that the lack of clear strategic goals of economic development of the state and adherence to such a strategy has led to an increase in the cost of servicing external pu blic debt, increasing the cost of attracting it and reducing the maturity. It is also proved that the lack of strategy together with the low level of fiscal, debt and monetary policy coherence are the main reasons for inefficient conversion of external public debt, as the main amounts of external government borrowing are not used to finance economic development, but to finance state budget expenditures and to repay old debts. The purpose of to the article is to study the theoretical and practical aspects of debt policy in the context of the COVID-19 pandemic in order to justify a new paradigm of Ukraine’s external public debt management policy. Results. Based on the analysis of major macroeconomic trends in Ukraine and identifying external debt problems, the latest paradigm of external public debt management policy is proposed, the essence of which is to subordinate debt policy to tactical and strategic goals of the national economy budget, debt and monetary policy, as well as in achieving effective conversion of external government borrowing to stimulate economic development. It is proposed to use a program-targeted method of external public debt management policy, which involves raising funds from international organizations exclusively to finance specific government programs. Perspectives. It is necessary to increase the efficiency of conversion of external government loans to finance capital investments from the State budget, which will use the foreign debt potential to stimulate Ukraine’s economic development.